Assessing the accuracy of the zygoma for estimating ancestry using geometric morphometrics in a South African sample - Tawha, Tafadzwa Primrose Rudo (Department of Pathology, 2020)
The large number of unidentified, decomposed and skeletonised remains found in South Africa (SA) necessitates relevant and reliable methods to assist in victim identification. Ancestry estimation from unknown skeletal remains is essential when reconstructing a demographic profile of a missing person. In the SA population, estimating ancestry is problematic as standards developed internationally rarely apply to the local, biologically heterogenous population. Craniofacial morphology is known to be ancestrally distinct and studies are yet to explore shape and size variation in the zygomatic bone of the SA population. The aim of this study was to assess ancestral variation in zygomatic shape and size in a SA population using three-dimensional geometric morphometric analyses. A sample of 158 individuals were analysed from Bantu-speaking (BA), European (EA) and Mixed Ancestral (MA) South African groups. Males were larger in size than females, but no size differences were observed between ancestral groups. Significant shape differences were observed between ancestral groups, while none were observed between males and females. BA and MA individuals had narrower, shorter and more anteriorly projecting zygomas than EA individuals. The zygoma was shown to accurately distinguish EA (84%) from BA (81%), and MA (80%) from EA (68%) individuals, but unreliably distinguished BA (60%) from MA (66%) individuals. This is likely correlated to the historical peopling of SA and historical forced racial classification. Age-related changes and antemortem tooth loss did not confound the ancestral variation in size, despite minor changes in zygomatic shape being associated with these two factors. These confounders did not impact ancestry estimation accuracies, further suggesting a minor impact on overall zygomatic shape. Furthermore, the patterning of ancestral variation in the zygoma revealed the need for further research to distinguish between the biologically heterogenous ancestral groups in SA.